Economical response of cultivation of lemon grass (C. flexuosus ‘CKP- 25’) under agroforestry system - Yadava, Anil Kumar (Indian Journal of Agroforestry, 2020)
Lemon grass was tested with three spacing and four different fertility levels under poplar (Populus deltoides 'G-48' Marsh.) for its performance in Kumaun foothills for two years (2004-06). The spacing 40X40cm and fertility level N150P40K40 proved to be superior in respect of number of tillers, plant height, herbage yield, oil yield and net profit over other treatments.AII the treatments have non-significant effect on the average oil content. The height and diameter of poplar increased significantly with increase in spacing of lemon grass and doses of N, P, K fertilizer over control.